Peran Industri Jasa Keuangan dalam Pembangunan Ekonomi Indonesia - Arifah, Husna; Meidy H, Moch. Fauzan; Surgawati, Iis; Rusliana, Nanang; Zahra Nasution, Fatimah (WELFARE Jurnal Ilmu Ekonomi, 2023)
The financial services industry is a sector that involves various institutions and companies that function as intermediaries in financial activities. The main objective of the financial services industry is to provide financial products and services to the public, such as loans, savings, investments, insurance, and fund management. These institutions are responsible for collecting funds from the public and allocating them to sectors that need financing. In addition, the financial services industry also plays a role in risk management, supervision, financial regulation, and facilitation of transactions in the capital market. This study aims to determine the role of the financial services industry in Indonesia. The type of research used is quantitative research with multiple linear regression analysis. The data used is secondary data obtained from the Central Statistics Agency (BPS) from 2011-2021 and official publications of Bank Indonesia. Based on the results of the study, exchange rates and inflation do not affect the role of the financial services industry. While interest rates affect the role of the financial services industry.Industri jasa keuangan adalah sektor yang melibatkan berbagai institusi dan perusahaan yang berfungsi sebagai perantara dalam kegiatan keuangan. Tujuan utama industri jasa keuangan adalah menyediakan produk dan layanan keuangan pada masyarakat, seperti pinjaman, tabungan, investasi, asuransi serta pengelolaan dana. Institusi ini bertanggung jawab dalam menghimpun dana dari masyarakat dan mengalokasikannya ke sektor-sektor yang membutuhkan pembiayaan. Selain itu, industri jasa keuangan juga berperan dalam menajemen risiko, pengawasan, regulasi keuangan, dan fasilitas transaksi di pasar modal. Penelitian ini bertujuan untuk mengetahui peran dari industri jasa keuangan di Indonesia. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan analisis regresi linear berganda. Data yang digunakan merupakan data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) tahun 2011-2021 dan publikasi resmi Bank Indonesia. Berdasarkan hasil penelitian nilai tukar dan inflasi tidak berdampak pada peran industri jasa keuangan, sedangkan suku bunga berpengaruh terhadap peran industri jasa keuangan.